Sperm DNA Fragmentation - Karavolos, Stamatios (Seminars in Reproductive Medicine, 2021)
Sperm DNA fragmentation refers to the accumulation of adducts as well as single- or double-strand DNA breaks and reflects the sperm DNA quality. Current data suggest that there are differences in sperm DNA quality among individuals with high or low fertility, and this observation has led to the idea that testing sperm DNA fragmentation could be a useful test of male fertility. However, sperm DNA fragmentation has become one of the most frequently debated topics in reproductive medicine, as there is no agreement about the optimal way to test for DNA fragmentation, the clinically significant level of sperm DNA fragmentation, as well as the best therapeutic options for infertile men. This article presents current evidence related to sperm DNA fragmentation and its role in managing male infertility.
Keywords: infertility; male; sperm DNA fragmentation